Інтернаціоналізми в українській термінології менеджменту - Козловська, Л.; Краснопольська, Н. (Культура слова, 2020)
Проаналізовано шляхи проникнення інтернаціоналізмів в
українську термінологію менеджменту. Досліджено особливості
функціонування міжнародних лексем у сучасній економічній
метамові. Визначено найбільш актуальні способи адаптації
міжнародних терміноодиниць субмови менеджменту. Акцентовано
на можливих варіантах семантичної трансформації міжнародних
лексем. Підтверджено словотвірну активність міжнародних
термінів. Схарактеризовано позитивні й негативні прояви
інтернаціоналізації досліджуваної терміносистеми. The article is dedicated to modern manifestations of various trends in
the choice of national or foreign name, especially in the economic discourse
of recent years, where the problem of terminological oppositions between
“specific” and “borrowed” has a place. The need to establish boundaries
and define the principles of linguistic tolerance for any terminological
units of language is among the most obvious questions that researchers
make efforts to answer, despite the fact that the internationalization of
terminological unit is an universal linguistic phenomenon. Therefore, the
ways how internationalisms are borrowed in the Ukrainian management
terminology are analyzed. The specific features of how international
terminological units are functioning in the modern economic metalanguage
with an emphasis on their ability to evolve are studied. There are
determined most relevant ways to adapt international terminological units
within the frameworks of management sublanguage, which either do not
undergo any changes or are adapted to the laws of the Ukrainian language
in different ways. The emphasis is made on available options to semantic
transformation of international international terminological units, a certain
part of which has become a lexical basis for the terminology under study.
There was is confirmed the international terms’ word-forming activity
basing on which various term-forming families are formed.
The purpose of this study is to clear up the issue what role the
international terms in the modern economic metalanguage as an important
factor in maintaining or upsetting the language tolerance balance. That is
why there are characterized the positive and negative manifestations of
how the terminology under study undergoes to internationalization. In the
research, an important emphasis is made on the obligatory consideration
of the balanced use criterion, which is applied for international vocabulary
in order to maintain the language tolerance level.